PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TGT BERBANTUAN GEOGEBRA DAN QUIZIZZ UNTUK MENINGKATKAN HASIL BELAJAR MATERI FUNGSI KUADRAT - Desti Anisa Zoraida; Kriswandani Kriswandani; Anna Royyanna Nikmah (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2023)
This Collaborative Classroom Action Research (CAR) aims to improve learning outcomes in Quadratic Function material using the cooperative learning type TGT (Teams, Games, and Tournament) which assisted by GeoGebra and Quizizz for class X students of SMA N 3 Salatiga. This CAR is carried out in 2 cycles based on the Kemmis and Taggart Theories which consist of 4 stages namely the planning, implementation, observation, and reflection. The subjects of this study were 34 students of class X SMA N 3 Salatiga. The data collection technique of this research uses observation and tests. The data were analyzed using descriptive and quantitative analysis. The results showed that there was an increase in the average value, in the pre-cycle was 77.7; cycle I was 81.6; and cycle II was 83.4. The percentage of classical completeness also shows an increase, students who have scored above KKM (75) in the pre-cycle was 58.06% (18 students), cycle I was 81.82% (27 students), and cycle II was 87.88%. (29 students).